2007
DOI: 10.1002/ange.200702690
|View full text |Cite
|
Sign up to set email alerts
|

Der indirekte elektrochemische Nachweis von Radikalen und Radikalfängern in biologischen Matrices

Abstract: [5] da mit dieser Methode paramagnetische Spezies selektiv bestimmt werden können. In einigen Fällen kann auch die UV/Vis-Spektroskopie zur Detektion bestimmter freier Radikale verwendet werden.[6] Auf der anderen Seite werden Antioxidantien gewöhnlich über ihre Reaktion mit freien Radikalen quantifiziert. Spektroskopische Techniken können für einige Radikale hoch selektiv und empfindlich sein, doch häufig ist es schwierig, sie in situ in chemischen oder biologischen Systemen anzuwenden. Eine Vielzahl von hoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A complementary method to characterize pristine archeological lead can be obtained using the voltammetric responses associated with the electrochemical reduction of O 2 in nonaqueous solvents. This is a well-known electrochemical process consisting of a one-electron reversible reduction leading to O 2 • – radical anion which, in the presence of water traces, is followed by subsequent oxidation of the superoxide radical anion to hydroperoxyde and hydroxide anions. , For our purposes, the relevant point to emphasize is that this electrochemical process provides an in situ method for generating reactive radicals, which then influence the electrochemical response of the electrode, in particular, its electrocatalytic behavior, as recently reported by Scholz et al Following this line of reasoning, one can expect that the O 2 to O 2 • – reduction process at lead-modified electrodes can be influenced by the nature of the modifier and that, conversely, the catalytic ability of the patinated metal can be modified as a result of the generation of radicals on its surface. Figure compares the CVs recorded at an unmodified electrode (dotted lines in parts a and b), for contemporary lead (continuous line in part a) and sample S.10 (continuous line in part b) immersed into air-saturated 0.10 M Bu 4 NPF 6 /MeCN.…”
Section: Resultsmentioning
confidence: 56%
“…A complementary method to characterize pristine archeological lead can be obtained using the voltammetric responses associated with the electrochemical reduction of O 2 in nonaqueous solvents. This is a well-known electrochemical process consisting of a one-electron reversible reduction leading to O 2 • – radical anion which, in the presence of water traces, is followed by subsequent oxidation of the superoxide radical anion to hydroperoxyde and hydroxide anions. , For our purposes, the relevant point to emphasize is that this electrochemical process provides an in situ method for generating reactive radicals, which then influence the electrochemical response of the electrode, in particular, its electrocatalytic behavior, as recently reported by Scholz et al Following this line of reasoning, one can expect that the O 2 to O 2 • – reduction process at lead-modified electrodes can be influenced by the nature of the modifier and that, conversely, the catalytic ability of the patinated metal can be modified as a result of the generation of radicals on its surface. Figure compares the CVs recorded at an unmodified electrode (dotted lines in parts a and b), for contemporary lead (continuous line in part a) and sample S.10 (continuous line in part b) immersed into air-saturated 0.10 M Bu 4 NPF 6 /MeCN.…”
Section: Resultsmentioning
confidence: 56%
“…Recently, we demonstrated that the hydroxyl radicals (OH•) of Fenton's reagent could remove self-assembled monolayers (SAMs) from gold electrodes [13], and surprisingly-could also dissolve asperities, thus leading to very smooth surfaces [14]. Herein we report that gold electrodes prepared by treatment with Fenton's reagent are also catalytically deactivated, almost certainly because the active sites on gold are selectively knocked out by the attack of the hydroxyl radicals.…”
Section: Introduction and Resultsmentioning
confidence: 97%
“…radicals in galvanostatic assays with simultaneous O 2 evolution [26][27][28]. A new approach to detect free radicals using an electrochemical procedure, in which the radicals destroy a well-defined molecular layer on an electrode, was proposed in [29]. Antioxidant activity and free radical scavenging ability of curcumin were investigated using two electrochemical methods and electron spin resonance (ESR) technique [30].…”
Section: Introductionmentioning
confidence: 99%